Proteksi Protein indigofera zollingeriana Menggunakan Ekstrak Tanin Kondensasi Dari Daun Sengon (Albizia falcataria) Terhadap Konsentrasi Amonia, Protein Total Dan Rumen Undegradaded Protein - Suci Maharani; Afzalani Afzalani; RA. Muthalib; Rahmi Dianita; Fachroerrozi Hoesni; Raguati Raguati (Universitas Djuanda, 2025)
The experiment was conducted to determine the effectiveness of condensed tannin from sengon leafs extract in protection of Indigofera zollingeriana leafs meal protein (IZLMP). The experiment was conducted using a complete randomize design consisting of five treatments, four replications and two experimental units. The treatments was P0 : IZLMP +0% condensed tannin (CT), P1: IZLMP + 0.5% CT, P2: IZLMP + 1% CT, P3: IZLMP + 1.5% CT, P4: IZLMP + 2% CT. Parameters measured was N-ammonia, total protein, rumen undegradable protein (RUP) and ruminal pH. The experimental result showed that protection of IZLMP with CT decreased ammonia concentration, increasing total, RUP value, and without effect on ruminal pH. The experiment concluded that the use of CT from sengon leaf extract at a level of 2% was effectively used to protect the IZLMP from degradation by rumen microbes.